No Evidence of CNS Inflammatory Activity in Individuals with post-COVID-19 Condition Experiencing Neurological Symptoms : Insights from TSPO-PET Imaging - Kuusi, Matilda (My University, 2024)
Background: Following recovery from COVID-19, some individuals experience long-term symptoms, referred to as post-COVID-19 condition (PCC). PCC often includes symptoms potentially of neurological or neuropsychiatric origin such as fatigue, brain fog and sleep disturbances. The underlying mechanisms of PCC symptoms are still largely unknown. Neuroinflammation has been suggested as a potential cause for the neurological symptoms of PCC; however, the research in PCC patients is limited. In current literature, increased translocator protein (TSPO) expression indicates increased microglial activation. Positron emission tomography (PET) imaging with TSPO-binding radioligands, such as [11C]PK11195, enables studying neuroinflammation in vivo. Methods: PET-imaging with [11C]PK11195 was performed to evaluate neuroinflammation in 20 participants with PCC compared to 13 healthy controls. [11C]PK11195 binding was assessed as distribution volume ratio (DVR). Blood biomarkers neurofilament light chain and glial fibrillary acidic protein were measured to assess neuroaxonal damage and evidence of astrocyte activation. Additionally, clinical assessments including neurological examinations and mental health questionnaires were conducted in the PCC group. Results: PCC participants did not exhibit increased [11C]PK11195 DVRs in the brain compared to healthy controls (p = 0.84), nor signs of neuroaxonal damage or astrocyte activation in PCC participants based on soluble biomarker analysis. However, [11C]PK11195 binding correlated with various variables in PCC participants. Higher quality of life was associated with decreased DVRs in hippocampus (ρ = -0.87, p < 0.001) and amygdala (ρ = -0.77, p = 0.0091), while increased depression and anxiety were associated with increased DVRs in these regions of interest. Conclusion: Other than brain inflammatory or neuroaxonal damage-related mechanisms are likely to contribute to the neurological symptoms experienced by the individuals with PCC.
Keywords: Post-COVID-19 condition, TSPO-PET, microglial activation, PET/MR, NfL, GFAP